PELATIHAN PENGGUNAAN MESIN BOR DI DESA NAGASARI - Pangestu, Soleh; Muis, Abdul; Rofieq, Ainur (Universitas Islam 45 Bekasi, 2024)
In an increasingly advanced development in the modern era today makes many people use machines in everyday life, one example is a drilling machine as a tool for making holes, for that drilling machine has a very important role in an activity in society. Of course, not all people have the skills to use drilling machines, especially school children, even though these machines are often in the surrounding environment. So by organizing community service through the Real Work Lecture (KKN) program in Nagasari Village, Serang Baru District, Bekasi Regency, it aims to train the community to be given awareness that it is important to have the skills to use the machines around to increase knowledge about the use of drilling machines. The method of implementing community service applies community education in the form of socialization and training. The impact of the success of the training program on the use of drilling machines is in the form of increasing technical skills in using drilling machines safely and efficiently, thus making potential skills for participants in managing the technical needs of household tools and others.